Impacts of carbon source type on metabolic pathways and microbial synergy in the simultaneous anammox and endogenous denitrification process - Wenlong Liu; Yuyan Zhang; Chenhao Yue; Jiaming Wang; Jun Li; Huijie Lu; Shilong He; Yongzhen Peng (Bioresource Technology, 2026)

A kidney-targeted MOF nanozyme combats calcium oxalate crystal-induced kidney injury - Xuhong He; Min Zhou; Zhengxin Liang; Shiyi Jin; Kunze Yu; Longxiyu Meng; Zhicong Tan; Jinming Xu; Jiaju Xu; Chongjun Xiang; Jingchao Wei; Wenjun Gao; et al. (Chemical Engineering Journal, 2026)

Amplification-free electrochemiluminescence biosensors based on peptide-templated gold nanocluster and CRISPR-Cas12a for Mycobacterium tuberculosis IS6110 detection - Lingjun Cheng; Qingmei Yang; Yuanyuan Yang; Yufeng Wang; Qingfei He; Zhiyan Zou; Canping Su; Jiaming Chen; Yinhuan Liu; Guolin Hong (Analytica Chimica Acta, 2026)

Sedimentary-diagenetic characteristics and genesis of the Upper Cambrian reservoirs in the Tabei area, Tarim Basin, NW China - Jun Li; Kaibo Shi; Bo Liu; Yongsheng Ma; Yuanchong Wang; Qing He; Jiaming Deng; Xichuan Men; Xiangyu Bai; Jianhao Hua (Journal of Asian Earth Sciences, 2026)

Multi-source accumulation pathways and drivers of soil organic carbon in coastal saltmarsh wetlands - Rui Zhong; Jiaming Yao; Lijie Pu; Jiayi Xie; Jiawei Tao; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Limin Yu; Gaili He; Sihua Huang (CATENA, 2026)

SMOTE-DNN algorithm for accurate recognition and classification of VAHs with minimal dataset requirements - Zijian Zhang; Jiaming Li; Wu Wang; Zhengmao Cao; Qingqing Ye; Chenyu Du; Ye He; Yanjuan Sun; Behzad Rezaei; Jianping Sheng; Fan Dong (Environmental Research, 2026)

Generalized traverse task scheduling based on THRO algorithm for AUV with energy-constrained - Qixin Sha; Rui Nian; Jiaming Zhang; Xiaoting Xu; Yue Shen; Bo He (Ocean Engineering, 2026)

Contrasting Resource-Use Strategies Under Tropical Stress: Linking Leaf Functional Traits to Fruit Biomass and Oil Yield in Camellia Oleifera - Wenjun Hong; Jindian Yang; Shufen He; Jiaming Song; Weiyu Chen; Zhitong Mai; Feifei Chen; Ling Lin; Chuanteng Huang (Tropical Plant Biology, 2026)

P300-mediated H3K56la delactylation promotes copper-induced steroidogenesis disorders in human ovarian granulosa cells - Panlin Wang; Jiaming Xiao; Bingbing Wang; Yi Zhang; Ke Xu; Yingjie Dou; Qianqian Guo; Ye He; Yan Sun; Wenxiang Wang (Journal of Hazardous Materials, 2026)

GIS-based Geotourism Route Design in Changbaishan Global Geopark - Junbo Zhao; Jinxin He; Jian Yi; Xiangjin Ran; Jiaming Li (Geoheritage, 2026)

Transcriptomics analyses reveal microgravity triggers estrogen synthesis amidst degeneration and aging in human ovarian granulosa cells - Changjian Yin; Jiaming Zhang; Zihang Cheng; Fang He; Haiquan Lu; Shigang Zhao (Life Sciences in Space Research, 2026)

Gaδ+-H active sites-driven reverse water gas shift reaction with high CO selectivity - Zhenzhong Tao; Huaixiang Li; Dedong He; Zijun Huang; Jun Liang; Jiaming Dong; Xiaohua Cao; Yongming Luo (Chemical Engineering Journal, 2026)

Engineering a Ga-Mn-Zr trimetallic oxide to modulate intermediates for highly selective light olefin synthesis from syngas - Xiuyun Jiang; Songpeng Cheng; Qingxiang Ma; Guangbo Liu; Jinhu Wu; Caixia Zhu; Reubroycharoen Prasert; Jiaming Liang; Xinghua Gao; Yingluo He; Guohui Yang; Noritatsu Tsubaki (Chemical Engineering Journal, 2026)

Cerium-modified Cu-SSZ-13 catalysts: Enhanced low-temperature activity and hydrothermal stability for efficient NOx reduction - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Journal of Environmental Chemical Engineering, 2026)

Multi-membrane integrated process enables efficient electrodialytic separation of alkaloids from aqueous extract of Caulis sinomenii - Lanlan Zhang; Xixi Ma; Tingting Xu; Shanshan Liu; Luna Chen; Jiaming Ji; Jinfeng He; Li Sun; Xiaocheng Lin; Chuanrun Li; Haiyang Yan (Desalination, 2026)

BnaCIPK9 homoeologs mediate the dosage-dependent regulation of seed oil in allotetraploid Brassica napus L - Nan Wang; Jingquan Tang; Xianfei Hou; Chengtao Quan; Jiaming Mai; Chao He; Rundong Chen; Baolong Tao; yuanguo Gu; Donghai Jia; Tingdong Fu; Jitao Zou; et al. (Theoretical and Applied Genetics, 2026)

Research on emission control performance of SSCR system based on multi-condition operation and three-high tests - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

Non-uniform salinity combined with localized nitrogen supply improves water use efficiency and fruit visual and storage qualities in tomato - Jinjing Liu; Zhenchang Wang; Yongfeng Huang; Yuexiong Wang; Weixing Wen; Kexin Chen; Yanmin Bi; Yating He; Jiaming You; Yaosheng Wang (Plant and Soil, 2026)

Sustainable development pathways of resource-based cities: the case of Xuzhou, China - Jiaming Zhang; Yunzhu Gui; Peiming He; Qingyun Tang (Environment, Development and Sustainability, 2026)

The role of ammonia in the global energy transition: opportunities and challenges in ammonia gas turbine technology - Shuai Chen; Bin Guan; Lei Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

High-efficiency catalytic removal of N2O from ammonia-fueled engine exhaust - Bin Guan; Zhongqi Zhuang; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; Tiankui Zhu; et al. (Fuel, 2026)

Design of a green certificate differentiated issuance mechanism based on renewable energy enterprises subsidy perspective: A case study of China - Qinliang Tan; Chaofan Shi; Jiabin Zeng; Zihan Jin; Yihong Ding; Jiaming He; Guangyu Qin (Energy Policy, 2026)

Synergistic effect in dual-site catalyst with silanol-stabilized Co2+-bonded Ni clusters for methane dry reforming - Zijun Huang; Dedong He; Han Xiao; Jun Liang; Jiaming Dong; Zhenzhong Tao; Xiaohua Cao; Dingkai Chen; Yongming Luo (Chemical Engineering Journal, 2026)

Multifactorial synergistic strategies mediate the biocontrol of Fusarium oxysporum-induced root rot by Bacillus velezensis SYL-3 - He Liu; He Huang; Yuzhe Wang; Mengnan An; Jiaming Bai; Jianquan Zhou; Haiyang Lan; Aiwei Qi; Baoan Song; Yuanhua Wu (Pesticide Biochemistry and Physiology, 2026)

Development of a modified CaCl2·6H2O shape-stabilized composite phase change material for the greenhouse soil-cooling system - Fuyu Qin; Runhua He; Lingzhi Zhong; Tao Xu; Jiaming Gao; Ximin Lin; Yi Yang; Weitao Shao (Energy and Buildings, 2026)

Fatty Acid-binding Protein 4 Exacerbates Blood–brain Barrier Disruption Through the JNK/c-Jun/MMP12 Pathway After Traumatic Brain Injury - Botao Ma; Dezhen Yang; Mengwu Tian; Shimei Dai; Zhuang Jing; Xuerui He; Xiaoqing Bao; Yinbo Long; Yu Gong; Yanling Dong; Jiaming Li; Gengshen Zhang; et al. (Molecular Neurobiology, 2026)

An Investigation of PSO-Optimized LSTM–Transformer Hybrid Model for Multi-Step Ship Motion Prediction - Yilu Peng; Qing Hai; Jiaming Zhang; Lingwei He; Yongyu Huang; Lin Du; Yiming Qiang (Journal of Marine Science and Engineering, 2025)
The advantages of hybrid models for time series forecasting have received significant attention, and several studies focus on and test their application in the seakeeping of ship motions. A hybrid model integrating an LSTM encoder and Transformer decoder (LT) is introduced to overcome the limitation of individual LSTM and Transformer: initially, the seakeeping response of the KCS ship was simulated by ANSYS-AQWA considering the sea state 3 and 4 simultaneously and established a dataset; secondly, three standalone baseline models (LSTM, Transformer, and TCN), and two hybrid models, LT and LT, with PSO-optimized hyperparameters (P-LT) were constructed and trained to forecast the seakeeping performance of ships with multiple steps of 30, 60 and 90; finally, the comparison between solo and hybrid models was made by different steps on RMSE, MAE and NRMSE evaluations to prove the advancement of LT and P-LT models. The P-LT hybrid model achieved consistent accuracy improvements compared with the best-performing individual models across different ship motions. Notably, RMSE reductions were observed at all prediction horizons (30, 60, and 90 steps), with maximum improvements reaching 13.54% for rolling, 11.83% for pitching, and 12.87% for heaving motions. This study provides both theoretical and practical support to ship motion prediction and demonstrates the potential of the proposed study as an effective engineering product for enhancing safety in ship operation.

Spatiotemporal changes in global cropland fire activity from 2003 to 2020 - Jiaming Wang; Xiaoting Zhong; Jie Zhao; Xiaofan Shen; Mengyu Wang; Junhao He; Xiaohan Meng; Qiuling Chen; Xinrui Lu; Liang Wang; Chao Yue (Global and Planetary Change, 2025)

Flexible CeO₂ surface engineering optimizes atomically dispersed Ru catalyst-support interaction for enhanced ammonia decomposition - Xuehan Hu; Bin Guan; Lei Zhu; Chenyu Zhu; Zhongqi Zhuang; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Machine learning-driven design for globally optimal performance of flexible pressure sensors - Yuhan Zhao; Zhanfeng Guo; Zetian Zhao; Hengbin Ding; Xiaoshi Li; Yihan Xu; Daixuan Wu; Zhongheng Sun; Yifan Li; Jiaming Li; Ruolan Zhao; Minghao Wang; et al. (Chemical Engineering Journal, 2025)

A Novel Approach for Fast Microplastic Quantification in Sediments Using Machine Learning—Spectrometer Combinations - Piao Yao; Jiaming Zhang; Bin Zhou; Yang Chen; Ding He (Water, Air, & Soil Pollution, 2025)

Snow-resilient mapping reveals three decades of surface water expansion on the Qinghai–Tibet Plateau - Shaofan Tang; Yilong Peng; Yongzhi Chen; Jiaming Liu; Pingping Zhang; Ying Zhang; Tingting He; Jianhua Li (Remote Sensing Applications: Society and Environment, 2025)

Spontaneous development and characterization of an endothelial-like cell line from mandarin fish Siniperca chuatsi - Jiaming Chen; Zhong Mi; Wenfeng Zhang; Panpan Luo; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

ZnP-H2Im glass for flame retardant wood: In situ vitrification and synergistic mechanisms - Zhipeng Zhang; Jinrong He; Yuzhang Wu; Jiaming Luo; Wei Qu (Chemical Engineering Journal, 2025)

Adipose-derived soluble fractions activated bioink promotes cutaneous repair and regeneration via mobilizing endogenous reparative cells - Wei Zhang; Jiaming Shao; Hanlei Zhou; Min Yang; Chenghao Cai; Fang He; Yiran Wang; Pengqin Xu; Sizhan Xia; Tingting Weng; Jialiang Wang; Ronghua Jin; et al. (Chemical Engineering Journal, 2025)

Mechanochemical treatment and valorization of hazardous fluorine from aluminum electrolyte in spent carbon anodes - Zhibo Liu; Zhenkun He; Bingqing Liu; Wenju Tao; Jiaxin Yang; Jiaming Li; Xianwei Hu; Zhaowen Wang (Journal of Environmental Chemical Engineering, 2025)

Pd/F-Al2O3 catalyst for N2O-NH3-SCR with ultrahigh low-temperature activity and resistance to inhibitory gases: Property research of being rich in oxygen vacancies with free electrons and reaction mechanisms - Zhongqi Zhuang; Bin Guan; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Carbon storage in typical ecosystems of coastal wetlands in Jiangsu, China: Spatiotemporal patterns and mechanisms” [Catena 254 (2025) 108882] - Rui Zhong; Lijie Pu; Jiayi Xie; Jiaming Yao; Lu Qie; Gaili He; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Zhongshun Gong; Yumeng Lu; Jiawei Tao; et al. (CATENA, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

Numerical Simulation of an Icebreaker Ramming the Ice Ridge - Wenbo Dong; Jiaming Chen; Yufei Zhang; Shisong Wei; Guangwei He; Fang Li (Journal of Marine Science and Engineering, 2025)
During polar navigation, icebreakers frequently encounter ice ridges, which can significantly reduce navigation efficiency and even pose threats to structural safety. Therefore, studying the ramming of ice ridges by the icebreaker is of great importance. In this study, the ice ridge is decoupled into the consolidated layer and the keel for modeling. The consolidated layer is simplified as layered ice, and an innovative hybrid empirical–numerical method is used to determine the icebreaking loads. For the keel, a failure model is developed using the Mohr–Coulomb criterion in combination with the effective stress principle, accounting for shear failure in porous media and incorporating both cohesion and internal friction angle. The ship is restricted to surge motion only. A comparative analysis with the model test results was conducted to assess the accuracy of the method, with the predicted ice resistance showing deviation of 9.85% in the consolidated ice area and 10.48% in the keel area. Ablation studies were conducted to investigate the effects of different ice ridge shapes, varying retreat distances, and different ship drafts on the performance of ramming the ice ridge. The proposed method can quickly and accurately calculate ice ridge loads and predict their motion responses, providing a suitable tool for on-site rapid navigability assessment and for the design of icebreakers.

Calibration is required for use of electromagnetic soil moisture sensors to accurately measure the water content of tree stems and sawdust - Jiaming Wang; Neil C. Turner; Hailong He (Plant and Soil, 2025)

Scale drop disease virus (SDDV) triggers ferroptosis both in mandarin fish (Siniperca chuatsi) and MFF-1 cells to facilitate virus infection via linking to transferrin receptor 1 (TfR1) - Jiaming Chen; Yuting Fu; Shuyi Chen; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

Task-Sequencing Optimization Using DSSA Algorithm for AUV with Limited Endurance - Qixin Sha; Jiaming Zhang; Yue Shen; Bo He (Journal of Marine Science and Engineering, 2025)
Efficiency is very important for robots when executing multiple tasks, especially for autonomous underwater vehicles (AUVs) with limited endurance. In order to improve efficiency, task-sequencing optimization, which focuses on achieving the optimal execution order of multiple tasks, is one effective way. In this paper, the classic lawnmower traverse task is taken as an example for optimization, and discrete salp swarm algorithm (DSSA), which combines salp swarm algorithm (SSA) and genetic algorithm (GA), is selected and applied to optimize task sequencing for one AUV. In the optimization process, there are two key problems that need to be solved. One is how to encode the individual chromosome and the other is how to perform genetic operations on chromosomes of different lengths. For the former problem, a two-layer encoding method is proposed to generate individuals in the population, in which identity number and entry point of different areas are encoded, respectively. For the latter problem, mutation and crossover operators are modified and extended to deal with individuals of variable length due to the limited endurance of AUVs. Simulation results show that the sequencing optimization can be achieved after finite iteration. Through comprehensive comparison, DSSA is finally implemented and verified in a physical AUV.

Carbon storage in typical ecosystems of coastal wetlands in Jiangsu, China: Spatiotemporal patterns and mechanisms - Rui Zhong; Lijie Pu; Jiayi Xie; Jiaming Yao; Lu Qie; Gaili He; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Zhongshun Gong; Yumeng Lu; Jiawei Tao; et al. (CATENA, 2025)

Evaluation of Geosites in Changbaishan Global Geopark based on Fuzzy AHP and TOPSIS - Jiaming Li; Jinxin He; Peng Lu; Xiangjin Ran; Jian Yi (Geoheritage, 2025)

Efficient lithium recycling from waste aluminum electrolytes through an environmentally friendly process - Jiaxin Yang; Wenju Tao; Jiaming Li; Jingui He; Zhaowen Wang (Chemical Engineering Journal, 2025)

Can wood harvest followed by forest regrowth enhance carbon sequestration of the forest sector in China? - Mengyu Wang; Chao Yue; Junhao He; Pengyi Zhang; Mengyang Xu; Yu Li; Jiaming Wang; Lele Wang; Can Xu (Global and Planetary Change, 2024)

SbSeI for high-efficient photocatalytic degradation of multiple pollutants - Kang Li; Yue Gao; Zhongxin Dong; Huibo Zhang; Xudong Fan; Lei Xu; Jie Huang; Feng Teng; Haibo Fan; Jiaming Song; Chunmei Zhang; Xuexia He; et al. (Environmental Research, 2024)

Environmentally friendly recycling of energy storage functional materials from hazardous waste lithium-containing aluminum electrolytes - Jiaxin Yang; Wenju Tao; Jiaming Li; Lingyu Kong; Shaohua Wu; Jingui He; Zhaoshun Liu; Yu Sun; Chao Fan; Zhaowen Wang (Chemical Engineering Journal, 2024)

Effects of elevated ozone, warming, and their interactions on the stem lodging resistance of rice under fully open-field conditions - Zaisheng Shao; Jiaming Gu; Longxin He; Yansen Xu; Bo Shang; Zhaozhong Feng (Agriculture, Ecosystems & Environment, 2024)

Nano ZnO modified amorphous carbon materials enabling long-cycle performance and high-capacity for lithium/sodium-ion batteries - Jiaming Liu; Zhen He; Tongfa Zhao; Yuqian Wei; lingpei Hou; Yunfei Song; Yuxin Wang (Chemical Engineering Journal, 2024)

Sensitive and quick electrochemiluminescence biosensor for the detection of reactive oxygen species in seminal plasma based on the valence regulation of gold nanoclusters - Lingjun Cheng; Yuanyuan Yang; Shaobin Lin; Canping Su; Mingming You; Yating Liu; Qingfei He; Jiaming Chen; Zhenyu Lin; Guolin Hong (Analytica Chimica Acta, 2024)

Evaluation of a novel attapulgite loaded sulfidized nanoscale zero-valent iron for immobilization of Pb in sediment: Performance, microenvironmental response, and mechanisms - Siqi Wen; Weilong Lin; Qi He; Yiqun Xu; Xiaoyu Shi; Jiaming Guo; Yang Gao; Wenjing Xue (Chemical Engineering Journal, 2024)

Water and fertilizer decision model for synergistic optimization of yield, quality and efficiency of cherry tomato based on combination evaluation - Rui Li; Jiaming Bai; Dayong Li; Xinru Ren; Daiwei He; Rongcheng Du; Ziqi Feng; Zhi Zhang (Computers and Electronics in Agriculture, 2024)

Amino-modified biochar-supported S-nZVI for Cr(VI) and total Cr removal from water: Parameter regulation, kinetic and mechanistic analysis - Yiqun Xu; Jiaming Guo; Siqi Wen; Xiaoyu Shi; Qi He; Weilong Lin; Yu Wang; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Water Process Engineering, 2024)

Multiple synergistic antibacterial melamine-impregnated paper based on nano Ag-doped ZIF-8 - Jinrong He; Wei Qu; Yun Feng; Jinrui Jiang; Jiaming Luo; Yuzhang Wu; Limin Peng (Chemical Engineering Journal, 2024)

Contributions of China's terrestrial ecosystem carbon uptakes to offsetting CO2 emissions under different scenarios over 2001–2060 - Mengyang Xu; Ziyu Zhang; Chao Yue; Jie Zhao; Pengyi Zhang; Mengyu Wang; Jiaming Wang; Hongfei Zhao; Jinyue Liu; Xianhui Tang; Junhao He (Global and Planetary Change, 2024)

Stepwise extraction of lithium and potassium and recovery of fluoride from aluminum electrolyte wastes through calcification roasting–two-stage leaching - Shaohua Wu; Wenju Tao; Hui Ge; Jiaxin Yang; Jiaming Li; Jingui He; Youjian Yang; Zhaowen Wang (Environmental Science and Pollution Research, 2024)

High performance self-assembled sulfidized nanoscale zero-valent iron for the immobilization of cadmium in contaminated sediments: Optimization, microbial response, and mechanisms - Yiqun Xu; Hongdou Liu; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Qi He; Weilong Lin; Yang Gao; Rongzhong Wang; Wenjing Xue (Journal of Hazardous Materials, 2024)

Clustering and optimization of nodes, beams and panels for cost-effective fabrication of free-form surfaces - Minghao Bi; Yuanpeng Liu; Tao Xu; Yunzhen He; Jiaming Ma; Zicheng Zhuang; Yi Min Xie (Engineering Structures, 2024)

Affecting factors and mechanism of removing antibiotics and antibiotic resistance genes by nano zero-valent iron (nZVI) and modified nZVI: A critical review - Wenjing Xue; Xiaoyu Shi; Jiaming Guo; Siqi Wen; Weilong Lin; Qi He; Yang Gao; Rongzhong Wang; Yiqun Xu (Water Research, 2024)

Fabrication of hyaluronic acid-altered gold complex delivery for head and neck squamous cell carcinoma therapy with high antitumor efficacy and low in vivo toxicity - Shizhi He; Jiaming Chen; Yanming Zhao; Ru Wang; Yurong He; Shaoshi Chen; Yifan Yang; Changyu Zhu; Jingyang Zhao; Jugao Fang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Ultra-sensitive and stable All-Fiber iontronic tactile sensors under high pressure for human movement monitoring and rehabilitation assessment - Ke Ma; Daojian Su; Bolong Qin; Junxian Li; Jiaming Zhong; Chi Zhang; Fuqin Deng; Gengzhe Shen; Weijia Yang; Yue Xin; Xin He (Chemical Engineering Journal, 2024)

Catalytic ozonation of multi-VOCs mixtures over Cr-based bimetallic oxides catalysts from simulated flue gas: Effects of NO/SO2/H2O - Peixi Liu; Hairong Tang; Jiaming Shao; Yong He; Yanqun Zhu; Elisabete C.B.A. Alegria; Zhihua Wang; Armando J.L. Pombeiro (Chemosphere, 2023)

Exploring year-to-year spatiotemporal changes in cycling patterns for bike-sharing system in the pre-, during and post-pandemic periods - Xiaoying Shi; Junjie Zhao; Jiaming He; Haitao Xu (Sustainable Cities and Society, 2023)

Revealing the travel community in the integrated system of free-floating bike and metro - Jiaming Zhong; Zhaocheng He; Jiemin Xie (Sustainable Cities and Society, 2023)

Engaging stakeholders in collaborative control of air pollution: A tripartite evolutionary game of enterprises, public and government - Jiaming Wang; Ling Jia; Pan He; Peng Wang; Lei Huang (Journal of Cleaner Production, 2023)

Full-scale experimental study on evacuation behavior characteristics of underwater road tunnel with evacuation stairs under blocked conditions - Kunkun Chu; Baochao Xie; Zhisheng Xu; Dan Zhou; Lu He; Jiaming Zhao; Houlin Ying (Tunnelling and Underground Space Technology, 2023)

Sphere2Vec: A general-purpose location representation learning over a spherical surface for large-scale geospatial predictions - Gengchen Mai; Yao Xuan; Wenyun Zuo; Yutong He; Jiaming Song; Stefano Ermon; Krzysztof Janowicz; Ni Lao (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

The carbon reduction effects of stepped carbon emissions trading and carbon capture and storage on hybrid wind-PV-thermal- storage generation operating systems - Yongmei Wei; Xinyu Wang; Jin Zheng; Yihong Ding; Jiaming He; Jian Han (Environmental Science and Pollution Research, 2023)

Dynamic retention of thallium(I) on humic acid: Novel insights into the heterogeneous complexation ability and responsiveness - Wanpeng Chen; Xiaoliu Huangfu; Jiaming Xiong; Hongxia Liu; Qiang He (Water Research, 2023)

Effect of gastrodin against cognitive impairment and neurodegeneration in APP/PS1 mice via regulating gut microbiota–gut–brain axis - Yuhe Zhang; Yan Chen; Shushu Yuan; Qingxia Yu; Jianjiong Fu; Luyun Chen; Jiaming Liu; Yuping He (Experimental Brain Research, 2023)

A mandarinfish Siniperca chuatsi infection and vaccination model for SDDV and efficacy evaluation of the formalin-killed cell vaccine in yellowfin seabream Acanthopagrus latus - Yuting Fu; Yong Li; Jiaming Chen; Fangzhao Yu; Xiangrong Liu; Weixuan Fu; Hongrun Pan; Wangdong Li; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A data-driven support system for the efficient schedule delay management of the ultra-high-voltage projects considering subjective risk preferences - Yunna Wu; Jiaming He; Yijia Liao; Yao Tao; Fangtong Liu; Jianli Zhou (Sustainable Cities and Society, 2023)

Depth-dependent drivers of soil aggregate carbon across Tibetan alpine grasslands - Junxiao Pan; Jiawei Shi; Dashuan Tian; Ruiyang Zhang; Yang Li; Yunlong He; Lei Song; Song Wang; Yicheng He; Jiaming Yang; Chunxue Wei; Shuli Niu; et al. (Science of The Total Environment, 2023)

Antibacterial anodic aluminium oxide-copper coatings on aluminium alloys: preparation and long-term antibacterial performance - Jiahuan Chen; Zhen He; Jiaming Liu; Yuxin Wang; Michael Hodgson; Wei Gao (Chemical Engineering Journal, 2023)

Improving the detection accuracy of the nitrogen content of fresh tea leaves by combining FT-NIR with moisture removal method - Jiaming Guo; Han Huang; Xiaolong He; Jinwei Cai; Zhixiong Zeng; Chengying Ma; Enli Lü; Qunyu Shen; Yanhua Liu (Food Chemistry, 2023)

Topology optimization of ribbed slabs and shells - Jiaming Ma; Yunzhen He; Zi-Long Zhao; Yi Min Xie (Engineering Structures, 2023)

Improved catalytic activity and stability of Cu/ZnO catalyst by boron oxide modification for low-temperature methanol synthesis - Fei Chen; Jiaming Liang; Fan Wang; Xiaoyu Guo; Weizhe Gao; Yasuharu Kugue; Yingluo He; Guohui Yang; Prasert Reubroycharoen; Tharapong Vitidsant; Noritatsu Tsubaki (Chemical Engineering Journal, 2023)

Analysis and intervention of heatwave related economic loss: Comprehensive insights from supply, demand, and public expenditure into the relationship between the influencing factors - Peng Wang; Wendi Zhang; Jiawen Liu; Pan He; Jiaming Wang; Lei Huang; Bing Zhang (Journal of Environmental Management, 2023)

TP-DDI: A Two-Pathway Deep Neural Network for Drug–Drug Interaction Prediction - Jiang Xie; Chang Zhao; Jiaming Ouyang; Hongjian He; Dingkai Huang; Mengjiao Liu; Jiao Wang; Wenjun Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2022)

A novel facial attractiveness evaluation system based on face shape, facial structure features and skin - Jian Zhao; Miao Zhang; Chen He; Xie Xie; Jiaming Li (Cognitive Neurodynamics, 2020)

Study of mosaicism of Pyropia yezoensis - Yuan He; Wei Zhou; Jiaming Li; Songdong Shen (Marine Biology Research, 2019)

A spatial-temporal analysis of urban recreational business districts: A case study in Beijing, China - He Zhu; Jiaming Liu; Chen Chen; Jing Lin; Hui Tao (Journal of Geographical Sciences, 2015)

Synergistic effect of EMS1-shRNA and sorafenib on proliferation, migration, invasion and endocytosis of SMMC-7721 - Jiaming Zhou; Li Chen; Yixin Zhang; Yuanyuan Wu; Guilan Wang; Song He; Zhongying Guo; Yingze Wei (Journal of Molecular Histology, 2014)